Efektivitas Penerapan e-ABK dalam Menganalisis Beban Kerja Pegawai di RSUD Dr. Mohamad Soewandhie Kota Surabaya - Myvara, Veren; Wibawani, Sri (VISA: Journal of Vision and Ideas, 2024)
This research aims to determine the effectiveness of implementing e-ABK at RSUD Dr. Mohamad Soewandhie, Surabaya City. This research is descriptive research with a qualitative approach, with data collection techniques through observation, interviews and documentation studies. This research analysis uses Campbell's effectiveness theory including program success, target success, satisfaction with the program, level of input and output and achievement of overall goals. The research results show that 1). The e-ABK program has succeeded in helping leaders analyze employee workload; 2). The success of the target has not been fully optimal, because there are still problems with several employees who still have difficulty operating the e-ABK application, especially in filling workloads and accuracy in creating supporting data; 3). Satisfaction with the program was stated to be quite satisfactory for employees who were able to operate e-ABK, but a small number of employees tended to feel dissatisfied with the existence of this system because they had difficulty in the operating process and accuracy in generating supporting data. On the other hand, the leadership also stated that they were quite satisfied with the implementation of e-ABK; 4). At the input and output level, the application has been programmed to process input and output according to employee workload analysis needs; 5). In achieving the overall goal, it is quite good, but there are still some employees who do not understand or have the skills to use the e-ABK application and accuracy in creating supporting data. Thus, it can be concluded that the effectiveness of implementing e-ABK in analyzing employee workload at RSUD dr. Mohamad Soewandhie, Surabaya City is not yet fully effective because there are still problems, some employees still do not understand and are skilled in using the e-ABK application and are accurate in creating supporting data.